Relationship Between Gender, Education, Employment, and Income in The Formal and Informal Sector in Sukabumi - Soetji Andari; Ismail Nasar; Indra Tjahyadi (Westscience Press, 2023)
This study investigated the relationship between gender, education, employment, and income in the formal and informal sectors in Sukabumi. The study used a mixed-methods approach, incorporating both quantitative and qualitative methods. The quantitative component involved a survey of 500 households evenly divided between men and women and between urban and rural areas. The qualitative part involved interviews with key informants and focus group discussions with women and men in Sukabumi. The study found that women in Sukabumi have lower levels of education, are less likely to be employed, and earn less than men in both formal and informal sectors. Gender norms and attitudes significantly shape women's access to education, employment, and income. The study recommends that policies prioritize women's education and employment opportunities in formal and informal sectors to promote gender equality and reduce poverty.